The relationship between pre‐operative hypertension and intra‐operative haemodynamic changes known to be associated with postoperative morbidity1. (12th March 2018) - Crowther, M.; van der Spuy, K.; Roodt, F.; Nejthardt, M. B.; Davids, J. G.; Roos, J.; Cloete, E.; Pretorius, T.; Davies, G. L.; van der Walt, J. G.; van der Westhuizen, C.; Flint, M.; et al.
Summary: Hypertension is not consistently associated with postoperative cardiovascular morbidity and is therefore not considered a major peri‐operative risk factor. However, hypertension may predispose to peri‐operative haemodynamic changes known to be associated with peri‐operative morbidity and mortality, such as intra‐operative hypotension and tachycardia. The objective of this study was to determine whether pre‐operative hypertension was independently associated with haemodynamic changes known to be associated with adverse peri‐operative outcomes. We performed a five‐day multicentre, prospective, observational cohort study which included all adult inpatients undergoing elective, non‐cardiac, non‐obstetric surgery. We recruited 343 patients of whom 164 (47.8%) were hypertensive. An intra‐operative mean arterial pressure of < 55 mmHg occurred in 59 (18.2%) patients, of which 25 (42.4%) were hypertensive. Intra‐operative tachycardia (heart rate> 100 beats.min −1 ) occurred in 126 (38.9%) patients, of whom 61 (48.4%) were hypertensive. Multivariable logistic regression did not show an independent association between the stage of hypertension and either clinically significant hypotension or tachycardia, when controlled for ASA physical status, functional status, major surgery, duration of surgery or blood transfusion. There was no association between pre‐operative hypertension and peri‐operative haemodynamic changes known to be associated with major morbidity and mortality. These data, therefore, support the recommendation of the Joint Guidelines of the Association of Anaesthetists of Great Britain and Ireland (AAGBI) and the British Hypertension Society to proceed with elective surgery if a patient's blood pressure is < 180/110 mmHg.